Laser Spectroscopic Investigations of Praseodymium I Transitions: New Energy Levels. (17th September 2012) - Uddin, Zaheer; El Bakkali, Driss; Gamper, B.; Khan, Shamim; Siddiqui, Imran; Guthöhrlein, G. H.; Windholz, L.
Abstract : We report the discovery of about 140 new energy levels of the neutral praseodymium atom, found by means of laser-induced fluorescence spectroscopy. Their energy has been determined with an uncertainty of 0.010 cm −1 using a wave number calibrated Fourier-transform spectrum.